Empowering Nurses as Key Players in the Regional Fight Against Antimicrobial Resistance - Almanfaluthi, Muhammad (UM Purwokerto Press, 2025)
This study explores the differences in knowledge, attitude, and practice (KAP) across gender, experience, residence, and ethnicity among 316 nurses. Understanding these variations is essential to tailor effective interventions that promote better knowledge acquisition and application in the long battle against antimicrobial resistance. A cross-sectional study was conducted with 316 participants (89 males, 227 females) to assess KAP metrics. Data were analyzed using incidence rate ratios (IRR) to explore relationships between demographic factors and KAP scores. Correlation analyses were performed to determine the strength of relationships between knowledge, attitude, and practice across various subgroups, including gender, residence (rural/urban), experience levels, and ethnicity. Significant gender differences were found, with females scoring higher in knowledge (IRR=1.03, p=0.024) and attitude (IRR=1.03, p=0.030) than males. Urban participants had significantly higher knowledge scores than rural participants (IRR=1.19, p<0.001). Experience levels also impacted knowledge, with participants having 3-6 years of experience showing lower scores than those with over ten years of experience (IRR=0.89, p<0.001). Attitude positively correlated with knowledge and practice (p<0.05). The findings reveal notable disparities in KAP across gender, experience, and residence. Females and urban participants demonstrate higher knowledge and attitude, while experience correlates with greater knowledge. Interventions should target rural areas and less experienced individuals and focus on improving attitudes to drive better knowledge and practice outcomes. Tailored educational programs addressing these disparities are recommended for more equitable KAP improvements.